Comparative Protective Effects of N-Acetylcysteine, N-Acetyl Methionine, and N-Acetyl Glucosamine against Paracetamol and Phenacetin Therapeutic Doses–Induced Hepatotoxicity in Rats - Tahia H. Saleem; Nagwa Abo El-Maali; Mohammed H. Hassan; Nahed A. Mohamed; Nashwa A. M. Mostafa; Emaad Abdel-Kahaar; Azza S. Tammam (International Journal of Hepatology)
Background and Aims. Both paracetamol (PA) and phenacetin (PH) are analgesic and antipyretic agents. Part of phenacetin therapeutic activity is attributed to its metabolism into paracetamol. Paracetamol causes direct hepatic oxidative stress damage. The present study aimed to investigate the possible damaging effects of both PA and PH, when used in therapeutic doses, on rat liver and to compare the antioxidant and hepatoprotective effects of N-acetylcysteine (NAC), N-acetyl-methionine (NAM), and N-acetylglucosamine (NAG) against PA- or PH-induced hepatic damage. Methods. 90 male Wistar albino rats (120-140 gm) were undertaken, categorized randomly into 9 groups of 10 rats each, and administered by gavage for 2 weeks with DMSO 1% (controls), PA, PA+NAC, PA+NAM, PA+NAG, PH, PH+NAC, PH+NAM, and PH+NAG. Biochemical assays of malondialdehyde (MDA), nitric oxide (NO), reduced glutathione (GSH), total thiols, and alpha-fetoprotein (AFP) in liver homogenates and serum assays of ALT, AST, 8-hydroxy guanine (8-OH-Gua), and AFP were done. Also histopathological examinations of liver tissues in various groups were done. Results. PA and PH cause significant increase in hepatic levels of MDA, NO, and AFP and serum ALT, AST, and 8-OH-Gua levels, with significant decrease in hepatic GSH and total thiols. NAG and NAC significantly improve the PA- and PH-induced hepatic and blood, biochemical, and histopathological disturbances, respectively. Conclusions. Both PA and PH induce oxidative stress in rat liver within their therapeutic doses. NAG and NAC in pharmacological doses can antagonize the oxidative damaging effect of both PA and PH.